2021
DOI: 10.2147/jir.s339254
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin as a Potential Therapeutic Target in Immune-Mediated Diseases

Abstract: Progranulin (PGRN), a secretory glycoprotein consisting of 593 amino acid residues, is a key actor and regulator of multiple system functions such as innate immune response and inflammation, as well as tissue regeneration. Recently, there is emerging evidence that PGRN is protective in the development of a variety of immune-mediated diseases, including rheumatoid arthritis (RA), inflammatory bowel disease (IBD), type 1 diabetes mellitus (T1DM) and multiple sclerosis (MS) by regulating signaling pathways known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…GRN is expressed in macrophages and is the most influential element of this molecular network. It encodes progranulin, which participates in inflammation, wound healing, and lysosomal activity 56 . Increasing progranulin levels increased the proportion of regulatory T cells and reduced inflammation and apoptosis in acute lung injury models 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GRN is expressed in macrophages and is the most influential element of this molecular network. It encodes progranulin, which participates in inflammation, wound healing, and lysosomal activity 56 . Increasing progranulin levels increased the proportion of regulatory T cells and reduced inflammation and apoptosis in acute lung injury models 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh et al recently suggested that lysosomal exocytosis is an important mechanism for coronavirus egress. 53 56 Increasing progranulin levels increased the proportion of regulatory T cells and reduced inflammation and apoptosis in acute lung injury models. 32 Progranulin upregulation repressed fibrotic genes and reduced liver fibrosis in animal chronic liver disease models.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one complex biological activity involving PGRN in astrocytes and microglia is likely to occur in the condition of the NAc neuroinflammatory response and possibly result in surprising outcomes, but further investigation is needed. Finally, PGRN is a complex protein that may have pro-or antiinflammatory properties depending upon the extent of PGRN-regulated proteolysis and the generation of proinflammatory GRN peptides [76]. In cultures of primary human microglia, LPS-increased PGRN cleavage occurs intracellularly, resulting in PGRN production being suppressed while GRN production is increased and switching the role of PGRN in microglia from neurotrophic to inflammatory under inflammatory conditions [75], which is consistent with our evidence of the actions of PGRN in a mouse model of NAc neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Article published online: 2023-07-17 [5,6], immune cells [7], macrophages [8] and fibroblastic cell [5,6]. The type of disease and its key role in the inflammatory and non-inflammatory pathways in immune-mediated diseases are the main reasons why progranulin plays an important immunomodulatory role [9,10]. A global genetic screen lead to the identification of tumor necrosis factor receptor (TNFR) as the preferential progranulin (PGRN)-associated receptor; PGRN and TNF-α bind to TNFR1 with comparable affinity, and PGRN acts as an antagonist of the TNF-α/TNFR1 interaction [11].…”
Section: Serum-progranulinspiegel Und Krankheitsaktivität Bei Patient...mentioning
confidence: 99%